2008
DOI: 10.1007/s11999-008-0372-7
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic Joint Space Width in Patients with Crowe Type-I Dysplastic Hips

Abstract: Radiographic evaluation of preoperative joint space width is believed important to predict the long-term results of osteotomy. We asked whether joint space width differs in the supine and standing positions in patients with Crowe Type-1 osteoarthritis (OA) secondary to developmental dysplasia of the hip (DDH). Joint space width was measured in the supine and standing positions in 146 women and 16 men (231 hips) with OA. Subjects had a mean age of 46.7 years (range, 22-59 years). Differences were seen on radiog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…The results illustrated variations between supine and erect, AI values were greater, CEA smaller, and minimum JSW was reduced in the standing position (P < .001 all metrics) [46]. Okano et al (2008) [47] found significant differences in JSW in 162 OA hip patients when imaging people in supine and erect positions. In standing positions, patients were asked to stand in a comfortable position and distribute their weight equally on both feet, rotating their feet inwards by 15 AE5 .…”
Section: Impact Of Repositioning On Jsw and Ceamentioning
confidence: 85%
See 1 more Smart Citation
“…The results illustrated variations between supine and erect, AI values were greater, CEA smaller, and minimum JSW was reduced in the standing position (P < .001 all metrics) [46]. Okano et al (2008) [47] found significant differences in JSW in 162 OA hip patients when imaging people in supine and erect positions. In standing positions, patients were asked to stand in a comfortable position and distribute their weight equally on both feet, rotating their feet inwards by 15 AE5 .…”
Section: Impact Of Repositioning On Jsw and Ceamentioning
confidence: 85%
“…Supine images obtained using the same parameters resulted in the JSW being greater for supine positions (P < .0001). Moreover, patients with JSW more than 1 mm in the supine position decreased by more than 1 mm in standing, and the authors recommended standing position for the evaluation of hip pain [47].…”
Section: Impact Of Repositioning On Jsw and Ceamentioning
confidence: 99%
“…While standing radiographs may theoretically provide more accurate estimation of cartilage thickness by exposing cartilage to the same loading and hydration conditions which occur during weight-bearing activity (6), accurate measurements of hip JSW can be obtained on both on standing and supine radiographs(79). Standing radiographs have been shown to provide more accurate assessment of JSW in patients with dysplasia of the hip (10). In obese patients, abdominal pannus may project over the hip joint in the standing position and limit penetration of the x-ray beam with the effect of reduced image quality (7).…”
Section: Acquisition Methods and Techniquesmentioning
confidence: 99%
“…First, pelvic radiographs were obtained in the supine position; however, several investigators recommended the use of weightbearing radiographs in the standing position for evaluation of hip osteoarthritis [21,30]. In those investigators, weight bearing significantly decreased JSW in hips with osteoarthritis but had no significant influence in normal hips.…”
Section: Discussionmentioning
confidence: 99%
“…Since there are variations of intrinsic JSW depending on the location of the joint surface [10,13] and different locations in which joint space narrowing is most apparent predominantly superolaterally, superiorly and superomedially [3], we calculated two types of JSWs. First, global JSW was calculated as the minimum JSW of the overall joint surface between the lateral and medial edges of the acetabular roof, which were generally employed in previous investigations [7,9,21]; second, local JSW (medial JSW, middle JSW and lateral JSW) was calculated as the minimum JSW in the evenly divided one-third of the joint surface between the lateral and medial edges of the acetabular roof (Fig. 1e).…”
Section: Computational Measurementmentioning
confidence: 99%